ANALISIS SOSIAL, EKONOMI DAN DEMOGRAFI TERHADAP PENGGUNAAN ALAT KONTRASEPSI DI KABUPATEN SIAK - Prasetiya Adi; Maulida Yusni; Aqualdo Nobel (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to analyze the effect of age at first marriage, education, household income and number of children still alive on the duration of use of contraceptives in Siak Regency. The methods used in this research are correlation and quantitative methods. Quantitative descriptive analysis is a study that uses numbers. The data from the information examined in this study are: primary data. Methods of data analysis using multiple regression with the help of SPSS Version 20.00. The results of this study indicate that partially and simultaneously the variables of age at first marriage, education, household income and number of children have a significant effect on the duration of use of contraceptives in Siak Regency.Keywords: Age of first marriage, education, household income, number of children still alive, duration of use of contraceptives